CHEWING BETEL LEAVES (Piper betle Linn.): PREVENT ORODENTAL DISEASE AND COVID-19 - I Gusti Ayu Ari Agung; I Nyoman Panji Triadnya Palgunadi; Putu Ayu Mahendri Kusumawati; I Gusti Agung Ayu Hartini; Dewi Farida Nurlitasari (International Journal of Applied Science and Sustainable Development (IJASSD), 2021)
Betel (Piper betle Linn.) is available in most of South and Southeast Asia. Betel leaves has the function of healing wounds in traditional Balinese medicine. This habit of chewing fresh betel leaves which are wrapped together with the areca nut, mineral, catechu and tobacco, is traditionally known as “nginang”. The several research stated that the habit of chewing betel leaf together with tobacco and areca nut has led to oral cancer. This paper aims to inform readers that chewing betel leaf is actually beneficial for health, as long as it is consumed without tobacco and areca nut. This paper focuses on the prevent orodental disease, and COVID-19. This systematic review was conducted through three steps: (1) A search (on Pubmed, Google scholar and other journal databases with published articles from 2009 to 2020); (2) Read the title and abstract of the individual papers; (3) Determine whether these articles were from diverse backgrounds. The nutritional content of the betel leaves for orodental health and anti-COVID-19 are protein, essential oils, carbohydrate, vitamin A, B and C and mineral like Mg, K, Ca, Fe, I, P and Zn. Betel leaves contains potassium potential nutrition and antioxidants including chevibetol and allylpyrocatechol, act as anti-COVID-19. Betel helps to cure various orodental diseases such as mouth cancer, cariogenic, sores, toothache, halitosis etc. The researcher concluded that “nginang”, chewing of fresh young betel leaves without areca nut and tobacco is very good to be continued, because of its many benefits and very good properties, especially for overcoming orodental disease and COVID-19.